Android Educational Game Design for Indonesian Presidential History Learning: Desain Permainan Pendidikan Android untuk Pembelajaran Sejarah Presiden Indonesia - Bahri, Ari Syamsul; Astutik, Ika Ratna Indra (Indonesian Journal of Education Methods Development, 2025)
Background: Indonesia’s historical literacy, particularly regarding its Presidents and Vice Presidents, remains relatively low, requiring more engaging learning media. Specific Background: Android-based educational games offer wide accessibility and allow interactive historical learning experiences. Knowledge Gap: Existing studies have developed historical games, yet few integrate platformer mechanics with structured historical content and quizzes. Aim: This study aims to design an Android-based educational game introducing Indonesia’s Presidents and Vice Presidents using the Game Development Life Cycle (GDLC). Results: The game “Jejak Pemimpin Bangsa” was created with platformer gameplay, information boards as learning media, and quizzes as assessment features. Alpha testing through black box evaluation showed all functions performed properly, while beta testing with 14 respondents produced a feasibility score of 88.93%. Novelty: The game integrates narrative-based platformer design, historical information delivery, and embedded quizzes within GDLC workflows. Implications: The findings show that educational games can enhance accessibility to history learning and serve as a supportive medium for increasing public understanding of Indonesia’s leadership history. Highlights: The game combines platformer mechanics with historical content GDLC ensures structured game development Quizzes reinforce learning within gameplay Keywords: GDLC, Educational Game, Presidents, Android, History